2016
DOI: 10.3892/or.2016.4861
|View full text |Cite
|
Sign up to set email alerts
|

Emodin induces hepatocellular carcinoma cell apoptosis through MAPK and PI3K/AKT signaling pathways in vitro and in vivo

Abstract: Abstract. Emodin is an active ingredient derived from root and rhizome of Rheum palmatum L and many studies have reported that it exhibits anticancer effects in a number of human tumors. However, there is little information demonstrating the possible effects of emodin on the proliferation and apoptosis of hepatocellular carcinoma (HCC). In the present study, we show that emodin may inhibit the proliferation of SMMC-7721 cells in a dose-and time-dependent manner and induced apoptosis of cells in a concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 27 publications
7
42
0
Order By: Relevance
“…However, CA inhibited PP2A and MEK and ERK were not blocked leading to formation of phosphorylation of ERK counteracting apoptosis. The present finding consistent with those of several studies, which suggest that the activation of ERK or p38 triggers the proliferation and apoptosis of HCC cells . Zhao et al reports that methyl CpG‐binding protein 2 promote the proliferation of HCC cells through ERK1/2 activation and p38 inhibition .…”
Section: Discussionsupporting
confidence: 93%
“…However, CA inhibited PP2A and MEK and ERK were not blocked leading to formation of phosphorylation of ERK counteracting apoptosis. The present finding consistent with those of several studies, which suggest that the activation of ERK or p38 triggers the proliferation and apoptosis of HCC cells . Zhao et al reports that methyl CpG‐binding protein 2 promote the proliferation of HCC cells through ERK1/2 activation and p38 inhibition .…”
Section: Discussionsupporting
confidence: 93%
“…A recent study also showed that emodin may suppress hepatocellular carcinoma growth and improve liver and kidney function in experimental mice without an obvious change in body weight, indicating that emodin may be an effective and safe drug for the treatment of hepatocellular carcinoma [31]. To see whether emodin has the potential to improve AML therapy in vivo, we established an AML xenograft mouse model with highly tumorigenic leukemia HL-60/H3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…1) is a naturally occurring anthraquinone derivative, which is found in a variety of tradition Chinese herbs including Rheum palmatum (9), Polygonum cuspidatum (10), Polygonum multiflorum (11) and Cassia occidentalis (12). Modern pharmacological studies have revealed that emodin possesses anti-proliferative effects on various cancer cells, such as pancreatic cancer (13), breast cancer (14), hepatocellular carcinoma (15), lung carcinoma (16), gastric carcinoma (17) and prostate cancer (18). Furthermore, this drug has also been reported to exhibit antiviral (19), antibacterial (20), anti-allergic (21), anti-osteoporotic (22), anti-diabetic (23), immunosuppressive (24) and neuroprotective (25) activities.…”
Section: Introductionmentioning
confidence: 99%